Creatine kinase rate constant in the human heart measured with 3D‐localization at 7 tesla. Issue 1 (31st August 2016) - Clarke, William T.; Robson, Matthew D.; Neubauer, Stefan; Rodgers, Christopher T.
Abstract : Purpose: We present a new Bloch‐Siegert four Angle Saturation Transfer (BOAST) method for measuring the creatine kinase (CK) first‐order effective rate constant kf in human myocardium at 7 tesla (T). BOAST combines a variant of the four‐angle saturation transfer (FAST) method using amplitude‐modulated radiofrequency pulses, phosphorus Bloch‐Siegert B 1 + ‐mapping to determine the per‐voxel flip angles, and nonlinear fitting to Bloch simulations for postprocessing. Methods: Optimal flip angles and repetition time parameters were determined from Monte Carlo simulations. BOAST was validated in the calf muscle of two volunteers at 3T and 7T. The myocardial CK forward rate constant was then measured in 10 volunteers at 7T in 82 min (after 1 H localization). Results: BOAST k f CK values were 0.281 ± 0.002 s −1 in the calf and 0.35 ± 0.05 s −1 in myocardium. These are consistent with literature values from lower fields. Using a literature values for adenosine triphosphate concentration, we computed CK flux values of 4.55 ± 1.52 mmol kg −1 s −1 . The sensitive volume for BOAST depends on the B1 inhomogeneity of the transmit coil. Conclusion: BOAST enables measurement of the CK rate constant in the human heart at 7T, with spatial localization in three dimensions to 5.6 mL voxels, using a 10‐cm loop coil. Magn Reson Med 78:20–32, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.